After poststructuralism : writing the intellectual history of theory - Rajan, Tilottama; O'Driscoll, Michael J. (Michael James), 1964- (University of Toronto Press, 2002)
Tackles the issue of providing an intellectual history of theory, given the considerable continuity between theory and the history of ideas. The editors address this challenge with thirteen essays on a variety of theorists from Derrida to Zizek.